Naratif suspense : satu kajian ke arah pembentukan struktur yang lebih berkesan - Ezarisyirwan, bin Basri (Universiti Malaysia Sarawak (UNIMAS), 2007)
Audient is hanging on a film by threatening information. Suspense is one of the element could create the most efficacious threatening that will make you as the audient stay hours to the end of the story. The .film objective is to mesmerized audient. Research has been done to identify the secret ofmajor credible threatening and it is all in the .film through narrative and character.